The impact of delayed time to first CT head on functional outcomes after blunt head trauma with moderately depressed GCS. - Schellenberg, Morgan; Benjamin, Elizabeth; Cowan, Shaun; Owattanapanich, Natthida; Wong, Monica D.; Inaba, Kenji; Demetriades, Demetrios (European Journal of Trauma & Emergency Surgery, 2022)
Purpose: Recent work suggests patients with moderately depressed Glasgow Coma Scale (GCS) score in the Emergency Department (ED) who do not undergo immediate head CT (CTH) have delayed neurosurgical intervention and longer ED stay. The present study objective was to determine the impact of time to first CTH on functional neurologic outcomes in this patient population. Methods: Blunt trauma patients presenting to our Level I trauma center (11/2015–10/2019) with first ED GCS 9–12 were retrospectively identified and included. Transfers and those with extracranial AIS ≥ 3 were excluded. The study population was stratified into Immediate (≤ 1 h) and Delayed (1–6 h) CTH groups based on time from ED arrival to first CTH. Outcomes included functional outcomes at hospital discharge based on the Modified Rankin Scale (mRS). Results: After exclusions, 564 patients were included: 414 (73%) with Immediate CTH and 150 (27%) Delayed CTH. Both groups arrived with median GCS 11 and alcohol/drug intoxication did not differ (p > 0.05). AIS Head/Neck was comparable (3[3–4] vs. 3[3–3], p = 0.349). Time to ED disposition decision and ED exit were significantly shorter after Immediate CTH (2.8[1.5–5.3] vs. 5.2[3.6–7.5]h, p < 0.001 and 5.5[3.3–8.9] vs. 8.1[5.2–11.7]h, p < 0.001). Functional outcomes were slightly worse after Immediate CTH (mRS 2[1–4] vs. 2[1–3], p = 0.002). Subgroup analysis of patients requiring neurosurgical intervention demonstrated a greater proportion of moderately disabled patients with a lower proportion of severely disabled or dead patients after Immediate CTH as compared to Delayed CTH (51 vs. 20%, p = 0.063 and 35 vs. 60%, p = 0.122). Conclusions: Immediate CTH shortened time to disposition decision out of the ED and ED exit. Patients requiring neurosurgical intervention after Immediate CTH had improved functional outcomes when compared to those undergoing Delayed CTH. These differences did not reach statistical significance in this single-center study and, therefore, a large, multicenter study is the next step in demonstrating the potential functional outcomes benefit of Immediate CTH after blunt head trauma.